Cecal Gut Microbiota and Metabolites Might Contribute to the Severity of Acute Myocardial Ischemia by Impacting the Intestinal Permeability, Oxidative Stress, and Energy Metabolism - Sun, Lili; Jia, Hongmei; Li, Jiaojiao; Yu, Meng; Yang, Yong; Tian, Dong; Zhang, Hongwu; Zou, Zhongmei (Frontiers in Microbiology, 2019)
Emerging evidence highlights the role of gut microbiota in regulating the pathogenesis of coronary heart disease. Here, we performed 16S rRNA gene sequencing and UPLC-Q-TOF/MS-based metabolomics to investigate the gut microbiome and metabolomes of cecal contents in the isoproterenol (ISO)-induced acute myocardial ischemia (AMI) rats. As expected, considerable gut microbiota alterations were observed in the AMI rats compared with the control rats, paralleling with intestinal inflammation and apoptosis. In phylum level, the abundance of Firmicutes was significantly decreased, whereas the abundance of Bacteroidetes and Spirochaetae was strikingly enriched in the AMI group. In genus level, the significant alteration of genera Treponema 2, Rikenellaceae RC9 gut group, Prevotellaceae UCG-003 and Bacteroides were regarded vital contributors to the pathogenesis of AMI. These altered microbiota might influence the intestinal permeability and subsequently impair intestinal barrier and stimulate gut inflammation. Consistently, significantly metabolic differences of cecal contents between the AMI and control groups were revealed, and threonic acid, L-urobilin and L-urobilinogen were considered the most associated cecal metabolites with AMI. These strikingly altered metabolites were mainly related to energy metabolism and oxidative stress which could lead to apoptosis and further affect gut barrier. Ultimately, we revealed the potential link of these altered gut microbiota/metabolomes and intestinal inflammatory factors and apoptotic proteins and further confirmed their intimate connections with intestinal inflammation and gut barrier. Our findings depict uncovered relationship among the gut microbiome, cecal metabolomes and AMI. It is likely to develop a new prevention and diagnosis of AMI targeting the gut microbiota or intestinal metabolites.